Izquierdo, Antonio y Cornelius, Wayne A. (eds.) (2012). Políticas de control migratorio: Estudio comparado de España y EE.UU. - Ortega Rivera, Enrique (Documents d'Anàlisi Geogràfica, 2014)
Izquierdo, Antonio y Cornelius, Wayne A. (eds.) (2012) Políticas de control migratorio: Estudio comparado de España y EE.UU. Barcelona: Edicions Bellaterra, 387 p. ISBN 978-84-7290-563-4